Induksi Kalus Stroberi (Fragaria spp.) Melalui Aplikasi Asam 2,4-Diklorofenoksiasetat Secara in vitro - GUSTI ARYA JELANTIK DWIPAYANA; HESTIN YUSWANTI; IDA AYU MAYUN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Induction of Strawberry callus (Fragaria sp.) Through Application of 2,4 dichlorophenoxy acetic acid in vitroThe study aims to know the concentration of 2,4 Dichlorophenoxy acetic acid for the growth of callus the strawberries. This study was conducted at laboratorium of tissue culture of agriculture faculty, Udayana on January until May 2015. The compiled using a Randomized Complete Block Design (RCBD) with five repetition and five level of treatment combination that is (D0,D1,D2,D3,D4,D5). If in the result found significant effect then followed up with duncan test 5%. Data that can not be analyzed tabulated and discussed descriptively.The result shows that treatment of D2 give best growth that it showed at percentage of highest deflection (54,765), fastest swelling (12,70 hst), highest swelling procentage (49,34%) and lowest browning procentage (43,05%). Beside that eksplan able to produce callus at D2 treatment with combination of MS media and by giving of 2,4 D 1 ppm.